Comparing two cases of training practice - implications for trainers' professional development : chapter 12 - Grollmann, Philipp [Verfasser] (My University, 2010)
"The aim of this paper is to present grounded thoughts about the principal dilemmas and challenges of professional development when it comes to the structure and levels of trainers' work profiles. This is done on the basis of two cases that represent typical examples of training practice in German VET. The cases have been selected according to two criteria: they represent cases of good practice as well as two different company contexts: a large industrial plant on the one hand and a small enterprise that is rooted in a family-owned crafts context. In this regard, they represent two distinct typical examples of VET practice in the German apprenticeship system. Training practices were researched through a triangular approach that explores training practices through interviews with learners, trainers and training managers, which is explained in the second section. The research presented is part of a larger European project that aims at the development of a framework for professional development for trainers (TT-Plus). First results of this research will be outlined in the third section." (Autorenreferat, BIBB-Doku)
Keywords: P 3.2.1 Ausbilder; I 2.1 Deutschland; Ausbilder; Ausbilderqualifizierung; Professionalisierung; Best practice; Fallstudie; Bundesrepublik Deutschland